konstruksi wacana dakwah dan kepentingan dagang dalam isu pelonggaran sertifikasi halal produk AS:analisis wacana kritis media suaraislam.id - alfarizi cahya maulana; Siti Raudhatul Jannah; Kun Waziz (SAHAFA: Journal of Islamic Communication, 2026)
This study aims to analyze the construction of da’wah discourse and commercial interests in media coverage regarding the relaxation of halal certification for United States products on Suaraislam.id. This research employs a qualitative approach within a critical paradigm using the Critical Discourse Analysis (CDA) model developed by Norman Fairclough, which emphasizes three analytical dimensions: text, discursive practice, and social practice. The data consist of two news articles explicitly addressing the issue of halal certification relaxation and the rejection of trade agreements without halal certification. Data were collected through documentation and analyzed interpretatively to uncover the relationship between language, ideology, and power within media texts. The findings reveal that Suaraislam.id not only reproduces religious ideology by representing halal certification as a symbol of safeguarding faith and framing commercial interests as an external threat, but also constructs a discursive relationship that is oppositional and asymmetrical between the two. Da’wah discourse is positioned as the dominant normative framework in interpreting economic policies, while commercial interests are subordinated through the use of religious diction, symbolic opposition between religion and economy, and the prominence of religious authorities as sources of legitimacy. At the level of discursive practice, the media integrates journalistic functions with da’wah missions, whereas at the level of social practice, the coverage reflects tensions between economic globalization and the preservation of Islamic identity. This study confirms that Islamic media not only represent reality but actively construct and constrain public understanding through ideological discourse. These findings contribute to the development of Islamic communication studies, particularly in understanding digital media as a asite of contestation between economic interests and religious values